Efektifitas Bantuan Sosial Kementerian Sosial RI bagi Anak Yatim Piatu di Kota Tangerang - Putri, Alika; Hadiwibowo, Ahmad Jami; Subarkah, Milana Abdillah (Penerbit Minhaj Pustaka, 2025)
The Indonesian government through the Indonesian Ministry of Social Affairs has taken real action to help orphaned children in Indonesia continue to grow and develop and receive the right to a decent life. In Islam, orphans are special children and must be treated well. The Qur'an has explained the orders and obligations of Muslims in supporting and caring for them with sincere and sincere affection. Our attitude towards orphans should be based on the principles of compassion, justice and social responsibility. ATENSI, an abbreviation for Social Rehabilitation Assistance, is focused on providing direct support to beneficiaries to ease the economic burden on their families. Social rehabilitation which aims to meet the basic needs of society. This program provides direct support to beneficiaries. In the ATENSI program, the Ministry of Social Affairs uses a family, community and/or residential-based approach. Activities carried out in this program include: Support for meeting the needs of a decent living, social care, family support, physical therapy, psychosocial therapy. Empowered means being strong, capable, powerful, or having the intelligence to overcome something. In the context of society, being empowered means being independent and responsible. Abstrak Pemerintah Indonesia melalui Kementerian Sosial RI telah melakukan aksi nyata untuk membantu anak-anak yatim piatu di Indonesia agar tetap tumbuh dan berkembang mendapat hak kehidupan layak . Dalam Islam, anak yatim merupakan anak yang istimewa dan harus diperlakukan dengan baik. Al-Qur'an telah menjelaskan perintah dan kewajiban para umat muslim dalam menyantuni dan memelihara mereka dengan kasih sayang yang tulus dan ikhlas. Sikap kita terhadap anak yatim seharusnya didasarkan pada prinsip kasih sayang, keadilan, dan tanggung jawab sosial. ATENSI, singkatan dari Asistensi Rehabilitasi Sosial, difokuskan pada memberikan dukungan langsung kepada penerima manfaat untuk meringankan beban ekonomi keluarga mereka. Rehabilitasi sosial yang bertujuan untuk memenuhi kebutuhan dasar masyarakat. Program ini memberikan dukungan langsung kepada penerima manfaat,. Dalam program ATENSI, Kemensos menggunakan pendekatan berbasis keluarga, komunitas, dan/atau residensial. Kegiatan yang dilakukan dalam program ini meliputi: Dukungan pemenuhan kebutuhan hidup layak, Perawatan sosial, Dukungan keluarga, Terapi fisik, Terapi psikososial. Berdaya berarti berkekuatan, berkemampuan, bertenaga, atau mempunyai akal untuk mengatasi sesuatu. Dalam konteks masyarakat, berdaya berarti mandiri dan bertanggung jawab.